2018
DOI: 10.1111/iji.12367
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HLADQA1 and HLADQB1 genes in B lymphocytes, monocytes and whole blood

Abstract: Differential expression of HLA-DQA1 and HLA-DQB1 gene alleles was analysed in three different cell populations isolated from peripheral blood-B lymphocytes, monocytes and whole-blood cells. Interallelic differences in mRNA levels were observed: DQA1*03 alleles were among the most expressed in all cell types, whereas DQA1*05 alleles were least expressed in whole blood and monocytes and among the most expressed in B cells. For DQB1 gene, DQB1*06 group of alleles were the most expressed, and DQB1*02 group the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(54 reference statements)
1
7
0
1
Order By: Relevance
“…However, alleles in the rhesus macaque with significant cell type specific expression were found. Some HLA-C alleles with consistently higher expression have been found by qPCR (Bettens et al 2014); this has also been observed for some alleles of the class II genes HLA-DQB1 and HLA-DQA1 (Zajacova et al 2018).…”
Section: Introductionmentioning
confidence: 73%
“…However, alleles in the rhesus macaque with significant cell type specific expression were found. Some HLA-C alleles with consistently higher expression have been found by qPCR (Bettens et al 2014); this has also been observed for some alleles of the class II genes HLA-DQB1 and HLA-DQA1 (Zajacova et al 2018).…”
Section: Introductionmentioning
confidence: 73%
“…We previously reported on the interallelic differences of HLA-DQA1 and HLA-DQB1 expression in monocytes and B-lymphocytes [ 30 ]. Intriguingly, it was noted that HLA-DQA1*01 and HLA-DQB1*06 showed low expression levels compared to other alleles in monocytes and B-lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In current study, differential expression of HLA-DQA1 gene alleles was analyzed in three different cell populations isolated from peripheral blood B lymphocytes, monocytes, and whole-blood cells. DQA1*03 alleles were among the most expressed in all cell types, whereas DQA1*05 alleles were least expressed in whole blood and monocytes and among the most expressed in B cells ( 54 ). It was reported ( 55 ) that TNFSF13 could support leukemia cell proliferation in an NF-κB-dependent manner by binding TNFRSF17 and suppressed apoptosis.…”
Section: Discussionmentioning
confidence: 99%